Serum Transaminase Concentrations and the Presence of Irritable Bowel Syndrome Are Associated with Serum 25-Hydroxy Vitamin D Concentrations in Adolescent Girls Who Are Overweight and Obese - Khayyatzadeh, Sayyed Saeid; Vatanparast, Hassanali; Avan, Amir; Bagherniya, Mohammad; Bahrami, Afsane; Kiani, Mohammad Ali; Bahrami-Taghanaki, Hamidreza; Ferns, Gordon A; Ghayour-Mobarhan, Majid (Annals of nutrition and metabolism, 2017)
Vitamin D deficiency has become endemic globally and its etiology is complex. Few studies have investigated the determinants of serum 25-hydroxy vitamin D (25-OH D). The aim of this study was to investigate the association between lifestyle patterns, liver functional tests (LFTs), and the presence of irritable bowel syndrome (IBS) with serum 25-OH D in apparently healthy girls. This cross-sectional study was undertaken in 965 adolescent girls aged 12-18 years. IBS was diagnosed using the Rome III questionnaire. An electrochemiluminescence method was used to measure serum 25-OH D. LFTs were measured using commercial kits and an auto analyzer. Linear regression and univariate analyses were performed to determine the association between continuous and categorical variables with serum 25-OH D respectively. Serum 25-OH D was significantly higher in normal weight subjects compared to either overweight or obese subjects (9.5 ± 7.02 vs. 7.9 ± 5.7 ng/mL, p = 0.03). Physical activity level was positively associated with serum 25-OH D in overweight and obese subjects (β = 0.15, p < 0.05). An inverse relationship was found between the presence of IBS and 25-OH D in both normal (β = -1.95, p < 0.05), overweight and obese subjects (β = -1.83, p < 0.05). Serum alanine transaminase (ALT; β = -0.19, p < 0.05) and aspartate transaminase (β = -0.17, p < 0.05) were inversely associated with serum 25-OH in overweight and obese subjects. Individuals with IBS had significantly lower serum 25-OH D concentrations. In addition, there was an inverse association between serum ALT and 25-OH D. Prospective studies, and perhaps interventional trials, will be required to clarify these associations.